Triplet carbonyls: from photophysics to biochemistry - Cilento, Giuseppe; de Baptista, Roberto Casadei; Brunetti, Iguatemy Lourenço [UNESP] (Elsevier, 1994)
Triplet carbonyls can be generated not only from the thermal cleavage of dioxetanes, but also enzymatically from appropriate substrates. The excited species can phosphoresce with an intensity depending upon the extent of shielding from deactivating oxygen collisions, react and also transfer energy, thus promoting sensitized emission and sensitized photochemistry. © 1994.